1979 Research Results Southeast Kansas Branch Agricultural Experiment Station - K. W. Kelley; R. J. Johnson; L. W. Lomas; J. L. Moyer; R. E. Lamond (Kansas Agricultural Experiment Station Research Reports, 1980)
Southeast Kansas Experiment Station is in its 30th year of operation. The emphasis has changed over this period to reflect changes in agricultural emphases of the area. The professional research staff consists of four scientists, each with a broad area of research responsibility. Together they emphasize improvement in crop production, forage production, beef cattle production and soil and water management.
Keywords: corn; grain sorghum; soybeans; wheat; forage; soil; water management; beef cattle